The Authority Of The Public Prosecutor In Confiscation Of Asset For Perpetrators Of Money Laundering Criminal Acts With Offshore Conversion Scheme: Authority Of The Public Prosecutor In Confiscation Of Asset For Perpetrators Of Money Laundering Criminal Acts With Offshore Conversion Scheme - angelica laura (Faculty of Law, Universitas Pekalongan, 2025)
The purpose of this research is to analyze the law in Indonesia which regulates the confiscation of assets of perpetrators of money laundering crimes using overseas conversion schemes which place assets resulting from criminal acts abroad, as well as identifying the scope of the Public Prosecutor's authority in handling money laundering criminal cases with an offshore conversion scheme. By using normative juridical research methods, it was found that currently the main regulation for money laundering criminal cases is Law Number 8 of 2010 concerning the Prevention and Eradication of Money Laundering Crimes. Meanwhile, the authority of the Prosecutor as Public Prosecutor is regulated in Law Number 11 of 2021 concerning Amendments to Law Number 16 of 2004 concerning the Prosecutor's Office of the Republic of Indonesia. There are progressive steps in the preparation of legal regulations in the field of money laundering, namely the drafting of the Draft Law on Asset Confiscation which allows the Public Prosecutor as the executor of the judge's decision to carry out asset confiscation in rem, as well known as non-conviction based forfeiture asset, that means legal action against the assets themselves, not against to the asset itself. individual (in personam) as in ordinary criminal cases.